2021
DOI: 10.3390/ijms22063239
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Autoimmune Lesions Is Independent of Antibiotic Treatment in NOD Mice

Abstract: The relationship between autoimmunity and changes in intestinal microbiota is not yet fully understood. In this study, the role of intestinal microbiota in the onset and progression of autoimmune lesions in non-obese diabetic (NOD) mice was evaluated by administering antibiotics to alter their intestinal microenvironment. Flow cytometric analysis of spleen cells showed that antibiotic administration did not change the proportion or number of T and B cells in NOD mice, and pathological analysis demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, commensal bacteria have been implicated in modulating autoimmune responses against insulin-producing β cells and, hence, diabetes [20][21][22]. Broad-spectrum antibiotics mostly worsened diabetes [23,24,[36][37][38], except for the marginal protection reported in one study [24]. Interestingly, a mixture of broad-spectrum antibiotics, ampicillin, metronidazole, and neomycin administered to adult NOD mice failed to inhibit diabetes development despite decreasing the gut microbiome [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, commensal bacteria have been implicated in modulating autoimmune responses against insulin-producing β cells and, hence, diabetes [20][21][22]. Broad-spectrum antibiotics mostly worsened diabetes [23,24,[36][37][38], except for the marginal protection reported in one study [24]. Interestingly, a mixture of broad-spectrum antibiotics, ampicillin, metronidazole, and neomycin administered to adult NOD mice failed to inhibit diabetes development despite decreasing the gut microbiome [38].…”
Section: Discussionmentioning
confidence: 99%
“…Broad-spectrum antibiotics mostly worsened diabetes [23,24,[36][37][38], except for the marginal protection reported in one study [24]. Interestingly, a mixture of broad-spectrum antibiotics, ampicillin, metronidazole, and neomycin administered to adult NOD mice failed to inhibit diabetes development despite decreasing the gut microbiome [38]. Providing probiotics also yielded mixed results on protection against diabetes [39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Along with these reports that questioned the role autoimmunity plays in the microbiota dysbiosis of SS, one possible reason to explain the microbiota changes is that the alteration of the microbiome is the leading factor of clinical symptoms as well as the breakdown of autoimmune system. After all, other studies also reported that microbial dysbiosis can occur independent of salivary deficiency and SS can be developed independent of microbiome changes (18,30).…”
Section: Diversity Changes In Microbiotamentioning
confidence: 95%
“…Primary Sjogren's syndrome(pSS) is a complex autoimmune disease, which is characterized by the infiltration of lymphocytes from exocrine glands, leading to the dysfunction of gland secretion, and then a series of symptoms of gland injuries, such as dry mouth, dry eye and swelling of parotid gland, as well as extraglandular manifestations such as arthralgia, interstitial lung disease(ILD), renal tubular acidosis and primary biliary cholangitis(PBC),and part of patients have systemic manifestations, such as fatigue, fever and weight loss [1,2] . Until now, the pathogenesis of pSS has not been clarified.Generally speaking, the pathogenesis of pSS is related to environmental factors,genetic susceptibility and immune disorder.It is well known that pSS is mainly mediated by T cells and B cells, but innate immune cells such as NK cells also play an important role in the pathogenesis of pSS [3] .Recent studies have found that the expression of NK cells in peripheral blood or salivary glands of pSS patients or model mice was abnormal, which was related to the activity and severity of the disease [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%